2010
DOI: 10.1063/1.3456991
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on the lasing from a dye-doped two-dimensional hexagonal photonic crystal made of holographic polymer-dispersed liquid crystals

Abstract: Cataloged from PDF version of article.Temperature dependent lasing was demonstrated in a dye-doped two-dimensional hexagonal photonic crystal made of holographic polymer-dispersed liquid crystals (LCs) along Gamma M direction in TE polarization. A redshift in lasing peaks was observed as the temperature increased from 25 to 45 degrees C. The downward movement of photonic band of TE polarization, majorly caused by the decrease in the anisotropy of LC droplets with the increase in temperature, is responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…3 There are few reports on temperature tunable PCs, and among them only one paper concerns the tunability of a superprism. 4 A steering angle of 28°is obtained for a temperature variation of 95 K. Temperature tuning of the optical properties of PC cavities has been reported by Wild et al 5 More recently, Luo et al 6 showed temperature dependent lasing in a dye-doped 2D hexagonal polymer PC. The rest of the reported works demonstrate photonic band gap tunability.…”
mentioning
confidence: 81%
“…3 There are few reports on temperature tunable PCs, and among them only one paper concerns the tunability of a superprism. 4 A steering angle of 28°is obtained for a temperature variation of 95 K. Temperature tuning of the optical properties of PC cavities has been reported by Wild et al 5 More recently, Luo et al 6 showed temperature dependent lasing in a dye-doped 2D hexagonal polymer PC. The rest of the reported works demonstrate photonic band gap tunability.…”
mentioning
confidence: 81%
“…Both TE and TM modes existed in the lasing with similar intensities. Although the multi-peak lasing generation within H-PDLC is expected according to the previous reports of theoretical simulation [6] and experimental works [10][11][12], lasing in such a wide range has never previously been observed (previously lasing peaks were generally within a spectral range of less than 10 nm, measured at distance of about 1~2 cm away from the sample). Further moving the spectrometer far away from the sample to a distance of about 6 cm, the spatial pattern of the output laser beam is found to be separated into two spots, which are symmetric with respect to the x axis, and similar to a traditional rectangle (C) 2012 OSAtransverse mode pattern TEM 10 generated from a laser cavity with rectangle symmetry.…”
Section: Methodsmentioning
confidence: 98%
“…For dye-doped photonic crystal, the photonic crystal structure formed by H-PDLC acts as an optical cavity, while the doped dye molecules act as the laser gain medium. The electrically tunable and temperature dependent characteristics of lasing from dye-doped 2D H-PDLC PCs are also investigated [11,12]. However, to our knowledge, the angle dependent lasing from a 2D H-PDLC PC has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, H-PDLC devices can provide not only highly integratable capability with variety of geometric configurations, but also excellent stability compared to the completely fluidic LC based devices. Until now, tunable lasing properties from H-PDLC gratings in planar cells have been investigated extensively, such as electrical [6], thermal [24,25], and optical [26] tunable methods. As aforementioned the flexibility of H-PDLC, of interest is what's the lasing properties when the H-PDLC grating structures are prepared in a cylindrical geometry, such as photonic crystal fiber, micro capillary etc..…”
Section: Instructionmentioning
confidence: 99%